OBJECT OF STUDY OF CAUSATOLOGY - Turniyozov Bekhzod Nigmatovich (Ethiopian International Journal of Multidisciplinary Research, 2023)
In linguistic literature, when it comes to «causality», it is said that this term comes from the Latin word «causa», which means the cause of an action (impact). The causative connection is studied in linguistics from this point of view and is associated with the meanings of cause and effect in the analysis of causative situations. Examples of this are complex sentences with an effect clause and a cause clause, sentences with motivation and coercion, forms of the imperative voice of the verb, which are broadly studied under this term. With this in mind, we suggest that the field of linguistics that deals with the study of causative relations can be called causatology. The field of causatology has come a long way before it was formed historically and studied in linguistics.